Comparative study on optimum DG placement for distribution network - Jamian, J.J.; Aman, M.M.; Mustafa, M.W.; Jasmon, G.B.; Mokhlis, Hazlie; Bakar, A.H.A. (Badania porównawcze metod optymalizacji rozmieszczenia kogeneracji rozproszonej w sieci dystrybucji energii elektrycznej, 2013)
With the advent of restructuring in power system and the exponential growth in the load demand, the importance of Distribution Generation (DG) has been increased. The DG is used to reduce the power losses and also to improve the system stability. The non-optimum DG placement and sizing could result in increase power losses and instability of the power system. This paper presents the comparative study for DG allocation techniques based on three different indicators namely Active power VSI (P-VSI), Reactive power VSI (Q-VSI) and Power Losses Reduction (PLR) indicator. The performances of these indicators are also compared for optimal DG output, maximum loss reduction, improvement in voltage profile and improvement in voltage stability. Standard 12-bus and 33-bus radial distribution networks are used as a test system. From the analysis and results, it is found that PLR performance is better than P-VSI and Q-VSI indicators in DG allocation.